Surgical treatment options for benign prostatic obstruction: beyond prostate volume. Issue 1 (January 2022) - Deyirmendjian, Claudia; Elterman, Dean; Chughtai, Bilal; Zorn, Kevin C.; Bhojani, Naeem
Abstract : Purpose of review: Many surgical treatment options are available for patients who present with benign prostatic obstruction (BPO). This article reviews the current treatment options available and distinguishes them based on five clinical considerations: antithrombotic therapy, sexual function preservation, ambulatory procedures, anesthesia-related risks and duration of catheterization. Recent findings: A comprehensive review of the literature was performed on 10 BPO procedures. Laser enucleation of the prostate (LEP), bipolar plasma transurethral vaporization of the prostate and photoselective vaporization (PVP) of the prostate reduces the risk of bleeding, which is recommended for anticoagulated men. Ejaculatory function is more likely to be preserved following transurethral incision of the prostate, Rezūm, Aquablation, UroLift and iTind. Same-day discharge is possible for LEP, PVP and prostatic arterial embolization (PAE). For patients with high anesthesia-related risks, procedures compatible with local anesthesia (UroLift, Rezūm, iTind and PAE) should be favored. Catheterization duration is shorter with UroLift, PVP and LEP. Summary: BPO treatment options are growing rapidly. The optimal procedure for a given patient is based on factors such as associated risks, recovery and expected outcomes. Besides prostate volume, the clinical considerations in the present article can help elucidate the best surgical BPO treatment option for each patient based on their values, preferences, and risk tolerance.